Obesity and hyperlipidemia were associated with more severe synovitis and structural abnormalities as well as inferior functional outcomes in knee osteoarthritis: a retrospective comparative study - Kuo Hao; Juncai Wang; Yingzhen Niu; Fei Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Considering that the respective effects of obesity and hyperlipidemia on knee osteoarthritis (OA) have not been fully investigated, the purpose of this study was to determine the relationship of obesity or hyperlipidemia with the synovitis and structural abnormalities of knee OA, and the effect of obesity and hyperlipidemia on functional outcomes of total knee arthroplasty. Methods There were 99 OA patients without obesity and hyperlipidemia in Group 1, 100 OA patients only with obesity in Group 2, 98 OA patients only with hyperlipidemia in Group 3, and 97 OA patients with both obesity and hyperlipidemia in Group 4. Semi-quantitative synovial inflammatory markers were measured including effusion-synovitis, size and intensity of infrapatellar fat pad abnormality, and synovial proliferation score. The structural abnormalities of knee OA were evaluated using Whole-Organ Magnetic Resonance Imaging Score (WORMS). Functional outcomes were evaluated before surgery and at 2 years follow-up. Results There were significantly higher effusion-synovitis, size and intensity of infrapatellar fat pad abnormality, and synovial proliferation score, as well as higher cartilage, bone marrow edema, meniscus, and total WORMS scores in Group 2, Group 3, and Group 4 (P < 0.05), but with no significant difference between Group 2 and Group 3 (P > 0.05). Group 2, Group 3, Group 4 had significantly worse Western Ontario and McMaster Universities Osteoarthritis Index, Forgotten Joint Score, Oxford Knee Score, Knee Society Score at baseline and 2 years follow-up (P < 0.05), but with no significant difference between Group 2 and Group 3 (P > 0.05). There were significant associations of obesity or hyperlipidemia with all synovial inflammatory markers and cartilage, bone marrow edema, meniscus, and total WORMS scores as well as functional outcomes (P < 0.05). Conclusions Obesity and hyperlipidemia were associated with more severe synovitis and structural abnormalities of knee OA, as well as inferior preoperative and postoperative functional outcomes. The negative effects of obesity and hyperlipidemia on knee OA could be mutually enhanced. The findings emphasized the negative effects of obesity and hyperlipidemia on the symptoms and outcomes of knee OA, and highlighted the association of obesity and hyperlipidemia with synovitis.